Bayesowski wybór modelu w regresji wielomianowej - Biskup, Dariusz (Bayesian Model Choice in Multinomial Regression, 2007)
The paper presents the problem of model choice in multinomial regression. The Bayesian solution to this problem has been presented in which the optimal model choice is equivalent to finding the model that is the most probable one. Computation of the model probabilities has been performed using the general algorithm of Reversible Jump Markov Chain Monte Carlo, which has been adapted to the specific problem of multinomial regression.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 50-63